The role of cytokines and interferons during pregnancy - T. Е. Belokrinitskaya; Yu. A. Vitkovsky; N. I. Frolova (Фундаментальная и клиническая медицина)
Immune cells, cytokines, and interferons are key mediators that ensure the gestational process from implantation to childbirth. The coordination of their signaling pathways determines molecular interactions between the mother and the fetus, the physiological course of pregnancy and its outcomes, particularly in the context of maternal respiratory viral infections. Here we analyze current information on physiological and pathological roles of cytokines and interferons during gestation in both uncomplicated and complicated pregnancies. Disrupted cytokine signaling might significantly alter fetal and placental development, leading to pregnancy complications and birth defects.